Congenital smooth muscle hamartoma: visibility of the contraction. - Milano, A. (European Journal of Pediatric Dermatology, 2019)
Congenital smooth muscle hamartoma usually originates from the arrector pili muscle of the hair and this origin could justify its hypertrichosis. The latter, which is not always visible to the naked eye, but detectable by dermoscopic examination, facilitates as in the present case the differential diagnosis from connective tissue nevus. However, hypertrichosis creates problems of differential diagnosis with the hairy or hypertricotic nevus in which the skin does not appear infiltrated, with plexiform neurofibroma, which however has a different histology and with Becker nevus which appears or becomes more evident at puberty due to the androgenic stimulation. Its muscular nature and its contractility are responsible for another clinical sign, that is the thrill that manifests at palpation. However, the latter is not always noticeable; contractility may instead occur at inspection with narrowing and greater relief of the lesion.